Konformitas Teman Sebaya dalam Perspektif Multikultural - Rahmayanthi, Ranni (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
The aim of this study was to determine the conformity profile peers based on multiculture perspective. Participants in this study weres 76 students senior hig school consist of 32 boys student and 44 girls students. This research approach using quantitative approach, types of research using a cross sectional survey. The instruments used was a scale conformity peers. Data were analyzed using analysisMann-Whitney U with a score of 702,5 and a significance probability value of 0.414. Because the probability of significance 0.987 > 0.05, the results showed that there was no difference conformity peers in the boys student and girls student.